Peningkatan Kapasitas Pengelola Keuangan Badan Layanan Umum Daerah (BLUD) pada Puskesmas di Kabupaten Tanah Datar - Fauzan Misra; Ilmainir Ilmainir; Jonhar Jonhar; Elvira Luthan; Rahmat Kurniawan; Ihsani Mazelfi (Warta Pengabdian Andalas, 2019)
The Regional Public Service Agency (BLUD) has empowered financial managers in the Regional Government to understand and understand the financial reporting process. The application of BLUD can provide flexibility in financial/goods management. In the practice of preparing financial statements, most financial managers do not have an educational background in economics, so they have limitations in understanding the preparation of financial statements. This community service aims to provide more understanding to financial managers in local governments to be able to prepare the reports needed in the context of BLUD application. Participants who are financial managers positively welcomed the community service activities carried out. They also suggested that this activity could be carried out more intensively and that an application was created to facilitate the process of preparing the financial statements of regional governments implementing BLUD.